The impact of sleep on the recovery of sport injuries - Vermeir, P.; Leye, M.; Grymonprez, R.; Goethals, A.; Vermeir, R.; Bossche, L. V.; Mariman, A. (British Journal of Sports Medicine, 2021)
Background Sleep is important to elite athletes as it plays a key role in repair of cellular damage. In recent years, there has been increasing interest in the role of sleep in athletes.